1997
DOI: 10.1055/s-2007-979068
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 (7 - 36) Amide: Effects on Glucose Transport and Metabolism in Rat Adipose Tissue

Abstract: In rat adipocytes, GLP-1 (7-36) amide induced an increment in 2-deoxy-glucose uptake, which was additive to that of insulin. Furthermore, in rat fat, GLP-1 (7-36) amide provoked a rise in glycogen synthesis, glucose oxidation and utilization and lipogenesis, the increments being lower than those obtained with insulin. These data support the idea that GLP-1 exerts insulin-like effects on glucose metabolism in rat adipose tissue, as it does in rat hepatocytes and skeletal muscle, although with a lower potency th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 3 publications
1
28
0
Order By: Relevance
“…At this submaximal concentration, the combined effect of both peptides on both glycogen synthesis and glycogen synthase a activity was additive, whereas at 10 10 mol/l no further increment was detected, indicating that GLP-1 may share the insulinsignaling pathway at some post-receptor level. These in vitro effects were previously observed in skeletal muscle from normal ) and diabetic (Morales et al 1997) rats, mice (O'Harte et al 1997), and also in the rat myocyte cell line L6 (Yang et al 1998), rat adipocytes (Oben et al 1991, Miki et al 1996, Perea et al 1997) and mice adipocyte cell line 3T3-L1 . The activating action of GLP-1 on glycogen synthesis and synthase a activity in human myotubes was maintained after 48 h exposure to the peptide, which supports the long-term therapeutic value of GLP-1.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…At this submaximal concentration, the combined effect of both peptides on both glycogen synthesis and glycogen synthase a activity was additive, whereas at 10 10 mol/l no further increment was detected, indicating that GLP-1 may share the insulinsignaling pathway at some post-receptor level. These in vitro effects were previously observed in skeletal muscle from normal ) and diabetic (Morales et al 1997) rats, mice (O'Harte et al 1997), and also in the rat myocyte cell line L6 (Yang et al 1998), rat adipocytes (Oben et al 1991, Miki et al 1996, Perea et al 1997) and mice adipocyte cell line 3T3-L1 . The activating action of GLP-1 on glycogen synthesis and synthase a activity in human myotubes was maintained after 48 h exposure to the peptide, which supports the long-term therapeutic value of GLP-1.…”
Section: Discussionsupporting
confidence: 61%
“…In the adipose tissue of the rat, it was observed that GLP-1 not only exerts an action on lipid metabolismdose-dependently lipolytic and/or lipogenic (Ruiz-Gande et al 1992, Perea et al 1997) -but also, as in liver and muscle, that it stimulates parameters involved in glucose metabolism (Perea et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that GLP-1, at physiological concentrations, directly stimulates glycogen synthesis in rat skeletal muscle (44) and rat adipose tissue (45), which is accompanied by an increase in glycogen synthase-a activity (44), which will lower plasma glucose levels. Glycogen synthase-a activity is also increased in hepatocytes from normal and diabetic rats (46).…”
Section: Extrapancreatic Effectsmentioning
confidence: 99%
“…Glucagon-like peptide-1 (GLP-1) is an insulinotropic peptide that has been proposed as a possible tool for the therapy of type 2 diabetes (Gutniak et al 1992); it has incretin character and insulin-independent antidiabetic properties (Gutniak et al 1992, D'Alessio et al 1995, and mimics the effects of insulin on glucose metabolism in the skeletal muscle and liver from normal ) and diabetic rats (Morales et al 1997), and also in fat (Perea et al 1997, Villanueva-Peñacarrillo et al 2001a. In these extrapancreatic tissues, GLP-1 seems to act through specific receptors (Mérida et al 1993, Valverde et al 1993, Delgado et al 1995, Villanueva-Peñacarrillo et al 1995a,b, Yang et al 1998 which, unlike the pancreatic one (Thorens 1992), are not associated with an activation of adenylate cyclase , Yang et al 1998.…”
Section: Introductionmentioning
confidence: 99%